Towards a sociopoetics of the short-story genre in French-speaking sub-Saharan Africa - (:unkn) unknown (My University, 2020)
Long confined to the margins of literary history, the short-story genre in French-speaking Africa has often lacked visibility among critics. Between a long-standing latent disinterest and nascent scientific research today, the short-story has for too long been absent in the African literary field. However, this peripheral posture seems inaccurate and incongruous nowadays, when one revisits its historical trajectory, and especially when we consider the interest that some writers take in it. Having achieved its autonomy as a genre, the short-story can no longer be considered a « premature novel », an « illegitimate genre » etc. This obsolete and old-fashioned vision is here reassessed, and allows, somehow, to direct the critical gaze (on its forms, its favorite themes ...), towards a more objective conception, built from the latest developments of the genre. Like the other narrative forms, and perhaps even more elaborately, the short story, in the French-speaking world, addresses the authors’ social experiences, summarizes their vision of the world and shows the process of its evolution in Sub-Saharan Africa. It is the overwhelming evidence of the observed and experienced reality of the short-story writer in a given time period in the history of his society. The short-story genre takes on the task of bringing to light, with a touch of realism, the worries and phenomena behind the dislocations and transformations of African societies. Based on new social representations taking place in Africa, it bears witness to a transformed Africa, stubbornly oriented towards fundamentally modern structures. For this reason, this genre tends to claim a new perspective, based on a debate devoid of any bias which has impacted it so far.
Keywords: African Research